Evaluation of Improved Tef [Eragrostisteff /Zucc./Trotter] Production Technologies in Central High Lands of Ethiopia - Gemechu, Bekele; Besufekad, Amha (Engineering International, 2019)
A study was carried out to evaluate the performance of improved varieties of tef and production technologies in Becho district of Oromia, Centeral Ethiopia. Five improved tef varieties along with the local were selected and used as treatments (that is, Dega tef (T1), Guduru (T2), Kena (T3), Kora(T4),Quncho(T5) and Local (T6)) arranged  in a Randomized Complete Block Design (RCBD) with six replications using six farmers’ fields. Yield and yield related parameters were analyzed using SAS statistical software version 9.0. Economic analysis/profitability, preference/acceptability, gender and nutrition and environmental suitability data recording were performed to compare treatments advantages and identify the best performing varietity/ies. All the yield and yield related components were significantly different between the varieties at 5 % probability level %) except for plant height in which there was no significant difference among varieties. Variety Dega tef gave the highest grain yield   with average grain yield of 3610.6kg/ha followed by Quncho and Kora and also had about 40% yield advantage over the local variety with average grain yield of 2577.83kg/ha and had about 116.95%, 110.25% and 90.80 % yield advantage over the national, regional and zonal average yield of tef in 2016/2017 Meher season of CSA data respectively. Based on farmer’s preference analysis variety Dega tef had high acceptability (75%) followed by Quncho (73%) and Kora (70%). Guduru variety has the least in acceptability (21%). As the result from the economic analysis showed that Dega tef variety had the maximum net benefit (79,536.69birr/ha) followed by Quncho (67,106.97birr/ha) and Kora (63,746.96birr/ha). Variety Guduru had the least net benefit result of about 53,648.17birr/ha. Based on the rules of decision making and the integrated scoring set for technology validation, two of the three improved varieties meet the requirements to be recommended. Therefore, we recommend Dega tef, Quncho, and Kora varieties for Becho areas and other areas with similar agro-ecological conditions in the central highlands of Ethiopia.
Keywords: Becho; economic analysis; environmental suitability; farmers’ acceptability; gender aspect; integrated validation; protocol